Simulation Case: Cardiac Arrest After Carbon Dioxide (CO2) Embolism - Bryan Halverson; Mathew Malkin; John Lenart; Marissa Vadi (MedEdPORTAL, 2016)
Abstract Introduction In this simulated case, a 68-year-old female presents for laparoscopic surgery. She subsequently has a CO2 embolism after placement of the Veress needle, leading to cardiovascular collapse. This simulated case walks the participants through the diagnosis and management of this scenario and provides an opportunity for the learner to formulate a differential diagnosis, communicate and effectively implement a treatment plan, and mobilize additional resources during a crisis situation. Methods This simulation was created as part of our core Anesthesiology Simulation Curriculum. Carbon dioxide (CO2) embolism is a rare, but potentially life-threatening complication of laparoscopic surgery. The clinical presentation is variable, ranging from asymptomatic to cardiovascular collapse or death, and depends on the rate and volume of carbon dioxide entrapment within major vascular structures. This simulation requires the participant to quickly formulate a differential diagnosis, recognize a CO2 embolism, initiate treatment including Advanced Cardiac Life Support, and determine appropriate post-event patient disposition. Results While we provide a learner evaluation tool, it has not been formally validated for resident evaluation. Rather, the tool provides faculty members with information regarding overall knowledge gaps that should be highlighted during simulation debriefing. Discussion We aim to run this case as an interdisciplinary exercise involving general surgeons and operating room staff, as well as anesthesia providers. This will allow us to assess team dynamics and crisis resource management skills among health care providers who work together clinically. An interdisciplinary debriefing will allow learners to better understand the concerns and priorities of different care providers during a crisis situation.